Diedrick Brackens - darling divined - Norton, Margot ca. 20./21. Jh (New Museum, 2021)
Foreword /Lisa Phillips and Simone Wicha --Intimacy and divination /Diedrick Brackens in conversation with Margot Norton and Francesca Altamura --In the decadence of silence /Derrick Austin --Breath Act(s) /Danielle A. Jackson --On catfish /Veronica Roberts --Fixin' things, American wedding, For my own protection /Essex Himphill
Published on the occasion of an exhibition at the New Museum, New York, June 4-September 15, 2019 and The Blanton Museum of Art, Austin, Texas, October 17, 2020-May 16, 2021
Keywords: Brackens, Diedrick -- 1989-; Bildteppich; Textilkunst; Homosexualität -- Motiv; Brackens, Diedrick / 1989- / Exhibitions; Brackens, Diedrick / 1989- / Interviews; Textile crafts / 21st century; Textile crafts / Political aspects; African American gay men / Identity / In art; Homosexuality and art; Art, Modern / 21st century; Textile crafts; African American gay men; Identity; Ausstellungskatalog -- New Museum -- 04.06.2019-15.09.2019 -- New York, NY; Ausstellungskatalog -- Blanton Museum of Art -- 17.10.2020-16.05.2021 -- Austin, Tex.; Bildband